Analisis Kontribusi Pendapatan Rumah Tangga Petani Kopi (Suatu Kasus Petani Kopi di Desa Margamulya, Kecamatan Pangalengan, Kabupaten Bandung) - Izzuddin, Fahmi Akbar; Rochdiani, Dini (Universitas Galuh, 2024)
Coffee is one of Indonesia's leading commodities. Indonesia is the fourth largest coffee producing and exporting country in Indonesia. The high amount of coffee production and exports in Indonesia should have a positive impact, such as increasing the income of coffee farmers from coffee farming as well as household income of coffee farmers. In fact, the income contribution of coffee farmers from coffee farming tends to be low compared to income from other commodity farming as well as outside the agricultural sector. The purpose of this study was to determine the contribution of coffee farmer household income in Margamulya Village, Pangalengan District, Bandung Regency. The method used in this research is survey. Respondents were taken using simple random sampling technique, totaling 38 farmers. The sample population in this study was calculated using the Slovin formula and analyzed using descriptive analysis. The conclusion in this study shows that the income contribution of coffee farmers from coffee farming (45.00%) is moderate because it is more than equal to than 35% and less than equal to 70% of the total income contribution. The income of coffee farmers from coffee farming is higher when compared to the contribution of farmers' income from non-coffee farming (19.35%) and non-agricultural income (35.65%). There is a significant difference between the income of coffee farmers from agriculture and non-agriculture